Pembangunan Sistem Informasi Pendataan Rumah Tangga Miskin Kecamatan Tulakan Kabupaten Pacitan - Dyah Ayu Mustikowati . (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT: Activity Management Unit of Poor Households Tulakan District is a government agencytasked to collect data on poor households, with the existence of these governmental agencies will behelped to find the data of poor households. So far, data management still done conventionally,allowing the damage intentionally or unintentionally, and that data can be manipulated. In addition tothe search for the data takes a long time.With this praktikan providing information systems solutions making the data collection of poorhouseholds. Which aims to produce a collection of information systems of poor households basedcomputer that can assist the process of data collection reporting to the leadership of poor householdsare more accurate and more timely as expected and diiginkan by the user or the user. The methodused in the manufacturing information system is a collection of poor households observation method,interview method. While the development of a conceptual information system is a system analysis,system design, programming, testing programs, implementation of the program.Information systems data collection of poor households is built using Microsoft Visual Basic6.0 with Microsoft Access databases supported. With a system of collection of information is of poorhouseholds, is expected to help the process of data collection reports to the leadership of poorhouseholds.Keywords: Data Collection Information Systems of Poor HouseholdsABSTRAKSI: Unit Pengelola Kegiatan Rumah Tangga Miskin Kecamatan Tulakan adalah sebuahinstansi pemerintah yang bertugas melakukan pendataan rumah tangga miskin, sistem manualnyadirasakan tidak lagi memadai untuk penaganan beban kerja, khususnya pendataan rumah tanggamiskin. Keadaan demikian menuntut penggunaan sistem informasi berbasis teknologi komputer.Sistem informasi ini penulis namakan sebagai Sistem Informasi Rumah Tangga Miskin yang meliputiSistem Informasi Data Penduduk, Sistem Informasi Data Penduduk Miskin dan Sistem InformasiAnalisis Penduduk Miskin. Penelitian ini bertujuan untuk merancang sistem informasi pendataanrumah tangga miskin yang terkomputerisasi. Metode yang digunakan dalam pembuatan sisteminformasi pendataan rumah tangga miskin adalah metode observasi, metode wawancara. Sedangkanpengembangan sistem informasi secara konseptual adalah analisis sistem, perancangan sistem,pembuatan program, pengujian program, implementasi program.Sistem informasi pendataan rumah tangga miskin ini dibangun dengan menggunakan bahasapemrograman Microsoft Visual Basic 6.0 dengan didukung basis data Microsoft Acces. Denganadanya sistem informasi pendataan rumah tangga miskin ini, diharapkan dapat membantu dalammelakukan kegiatan kesejahteraan sosial khususnya dan Kecamatan Tulakan umumnya..Kata Kunci : Sistem Informasi Pendataan Rumah Tangga Miskin